Monitoring of gastric residual volume during enteral nutrition - Yasuda, Hideto (Cochrane Database Syst Rev, 2019)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To investigate the clinical efficacy and safety of monitoring GRV during enteral nutrition.